A new genus of the tribe Pambolini (Hymenoptera: Braconidae: Exothecinae) from the Papua New Guinea with a key to the World genera - Belokobylskij, Sergey A.; Villemant, Claire (Zootaxa, 2016)
A new distinctive genus Spathiophaenodus gen. nov. from the tribe Pambolini (Braconidae: Exothecinae), with type species Spathiophaenodus annae sp. nov. from Papua New Guinea, is described and illustrated. The original key to the World genera of the tribe Pambolini is provided.